Pengaruh Pengetahuan Keuangan Dan Materialisme Terhadap Perilaku Menabung Pada Mahasiswa Dengan Impulsive Consumption Sebagai Variabel Mediasi - Dian Junita Dewi; Syaikhul Falah; Kurniawan Patma; Agustinus Salle (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
This research aims to provide knowledge about the behavior of saving, and materialism in saving impulsive consumption as a mediation variable in undergraduate students of Cenderawasih University Department of Accounting and IAIN Fattahul Muluk Papua majoring in Economics. The study was conducted using primary data, by distributing the frequency to respondents. Sample place in this study is students of Cenderawasih University Department of Accounting As many as 38 respondents and IAIN Fattahul Muluk Papua 22 respondents number of students who have filled the license.The results of this study show that (1) There is an insignificant influence on financial knowledge with saving behavior. (2) There is a significant influence on materialism on saving behavior. (3) Impulsive consumption can mediate variable materialism to saving behavior.